2010
DOI: 10.4018/javet.2010100102
|View full text |Cite
|
Sign up to set email alerts
|

Improving Second Language Speaking Proficiency via Interactional Feedback

Abstract: Researchers have suggested that interactional feedback is associated with foreign/second language learning because it prompts learners to notice foreign/second language forms. Using Vygotsky's zone of proximal development and Long's interaction hypothesis as conceptual frameworks, this study explores the use of systematic explicit feedback to undergraduates (N = 1180) at three assessment points throughout one semester using digital voice recording technology for oral assessments. Results indicate that statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Such advances in the teaching and learning of languages have spawned a body of research centered on the multiple uses of emerging technologies and their potential uses within the context of oral proficiency and assessment (Chan, 2003;Kvavik, 2005;Volle, 2005;Zhao, 2005). This chapter is guided by my research with several colleagues on the integration of digital tools for oral language assessment Swanson, Early, & Baumann, 2011;Swanson & Schlig, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Such advances in the teaching and learning of languages have spawned a body of research centered on the multiple uses of emerging technologies and their potential uses within the context of oral proficiency and assessment (Chan, 2003;Kvavik, 2005;Volle, 2005;Zhao, 2005). This chapter is guided by my research with several colleagues on the integration of digital tools for oral language assessment Swanson, Early, & Baumann, 2011;Swanson & Schlig, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Among the research findings regarding the use of Audacity in S/FL teaching and learning, student performance anxiety had been found to decrease while learner confidence about their own success in the S/FL learning process had been found to increase (Swanson, Early, & Baumann, 2011). Additionally, the research indicated that instructors noted an increase in valuable instructional time, more flexibility when scoring student performances, and that having a digital artifact that was archivable led to more reliable scoring of student proficiency (Early & Swanson, 2008;Swanson & Schlig, 2010).…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%
“…The author's research exploring the use of Audacity for assessing student speaking performance began in 2006 as faculty members at Georgia State University (USA) began to develop procedures and pilot test different voice recording systems in order to examine student speaking proficiency in more than a dozen languages and the effects of immediate instructor feedback (Swanson & Schlig, 2010). After carefully examining a variety of options, the Wimba ® voice recorder (Wimba, 2008) was selected because it could be embedded in the course management system (uLearn).…”
Section: Research Using Audacity As a Digital Tool For Oral Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For S/FL teachers, classroom time is lost when assessing students using the traditional face-to-face method. Assessing students' speaking proficiency using integrated performance assessments using free and open source digital recording platforms holds promise for P-20 instructors as well as language learners (Early & Swanson, 2008;Kvavik, 2005;Swanson, Early, & Baumann, 2011;Swanson & Schlig, 2010;Volle, 2005;Zhao, 2005). Such performance assessments may be able to decrease students' perceptions of irrelevance of language learning tasks, increase the reliability of the assessment, and provide important artifacts that can be used to document student achievement in the target language.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%